2009
DOI: 10.1021/nn900884n
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Gelation Properties of Self-Assembling Peptide Amphiphiles

Abstract: Peptide amphiphiles (PAs) are self-assembling molecules that form interwoven nanofiber gel networks. They have gained lots of attention because of their excellent biocompatibility, adaptable peptide structure that allows for specific biochemical functionality, and nanofibrous assembly that mimics natural tissue formation. However, variations in molecule length, charge, and intermolecular bonding between different bioactive PAs cause contrasting mechanical properties. This potentially limits cell-delivery thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
117
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 54 publications
2
117
0
Order By: Relevance
“…Peptides have recently been used to generate tubular, fibrillar, micellar, or vesicular nanostructures due their amphiphilic nature. [14][15][16][17] For example, peptides with a hydrophilic head and a hydrophobic tail spontaneously self-assemble to form vesicular structures in aqueous solution. 18 Peptide aggregation may alter the overall conformation and presentation of the amino acid sequence that interacts with cell surface receptors, which adversely affects the osteoinductive potential of the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Peptides have recently been used to generate tubular, fibrillar, micellar, or vesicular nanostructures due their amphiphilic nature. [14][15][16][17] For example, peptides with a hydrophilic head and a hydrophobic tail spontaneously self-assemble to form vesicular structures in aqueous solution. 18 Peptide aggregation may alter the overall conformation and presentation of the amino acid sequence that interacts with cell surface receptors, which adversely affects the osteoinductive potential of the peptide.…”
Section: Introductionmentioning
confidence: 99%
“…Such triggers include light, 171,172 heparin, 173 calcium, 174 cis-platin 175 and counter ion screening. 176 In contrast to the Fmoc-peptide derivatives discussed in section 4.1, PAs have not been used extensively to create 90 particularly strong gels (G′ typically around 200 Pa or lower, 127 although there are exceptions 77 ) and have generally been used as biomedical scaffolds. Some work has been undertaken, however, to optimise the strength of PA hydrogels.…”
Section: Peptide-amphiphilesmentioning
confidence: 99%
“…This carefully controlled study showed, for the first time, that additives can be used to strengthen PA hydrogels at no 10 detriment to structural conformation. More recently, Anderson et al 127 showed that a biologically inert PA could be effectively mixed with a bioactive PA to enhance structural stability of the final hydrogel whilst maintaining the material"s biological function. In some cases, the cell-binding 15 PAs were not able to form standing hydrogels without the incorporation of the structural PA additive, demonstrating the value of this approach for cell encapsulation and other tissue engineering applications.…”
Section: Peptide-amphiphilesmentioning
confidence: 99%
“…11,13 The nanomatrix can be self-assembled into two-dimensional coatings or three-dimensional nanomatrix gels. [18][19][20] It has been shown to promote endothelial cell adhesion and proliferation 11,12 as well as endothelial progenitor cell adhesion and differentiation.…”
mentioning
confidence: 99%
“…14 CONH-GTAGLIGQ-KKKKK] were prepared using the Fmoc chemistry in the Advanced Chemtech Apex 396 peptide synthesizer (AAPPTec, Louisville, KY, USA) and subsequently were alkylated at the N-termini with palmitic acid by a manual coupling reaction for 24 hours at room temperature. 18,20 To alkylate with palmitic acid, a mixture of o-benzotriazole-N,N,N,N′-tetramethyluronium hexafluorophosphate, diisopropylethylamine, and dimethylformamide was used, and cleavage and deprotection were achieved using a mixture of trifluoroacetic acid, deionized water, triisopropylsilane, and anisole (40:1:1:1) for 3 hours at room temperature. The peptide amphiphiles precipitated in cold ether were lyophilized and characterized by matrix-assisted laser desorption ionization time of flight mass spectrometry.…”
mentioning
confidence: 99%